Reforming the regional agricultural management system of the BSSR: The turns of the N. S. Khrushchev “great decade” - Elizarov, Sergey A. (Известия Саратовского университета. Новая серия. Серия: История. Международные отношения, 2025)
The main directions (decentralization and centralization) and specific forms of reorganization of agricultural management bodies as an element of the new state agrarian policy in 1953-1964, their practical implementation in the Byelorussian SSR are considered. It is noted that the most significant changes occurred at the district level as the closest to the direct business entities.